GALBA TRUNCATULA INDUCED TO INFECTION WITH MIRACIDIA OF FASCIOLA HEPATICA, COLLECTED IN HUAYLLAPAMPA, SAN JERÓNIMO, CUSCO, PERU - Iturbe Espinoza, Paul (2012)
Galba truncatula snails were obtained from January to April 2011, from a sub urban biotope (Huayllapampa) district of San Jeronimo, Cusco, Peru, and considered hyperendemic. They were grown in an aquatic environment. They were experimentally infected (n= 215) with miracidia of Fasciola hepatica. The eggs were obtained from the gallbladder and bile ducts of three sheep with fasciolosis, screened and washed in boiled water cooled to incubate at a constant temperature of 26°C. The resulting collection of snails had an abundance of catch per unit effort of 150/h. Shells ranged between: 3.5 to 7.0 mm long, 2.2 to 3.6 mm in width. A survival 75.81%, of which 71.78% showed infection with F. hepatica was noted.